Failure of oral Tyrosine supplementation to improve exercise performance in the heat - Tumilty, L.; Davison, G.; Beckmann, M.; Thatcher, R. (Medicine & Science in Sports & Exercise, 2014)
Purpose: Acute oral tyrosine administration has been associated with increased constant-load, submaximal exercise capacity in the heat. This study sought to determine whether self-paced exercise performance in the heat is enhanced with the same tyrosine dosage.